ONTOLOGINIS SKIRTUMAS IR METAFIZIKA. - Saldukaitytė, Jolanta (Problems / Problemos, 2010)
The problem of the "ontological difference" and its relation to metaphysics in Heidegger's philosophy is discussed. The ontological difference is presented as the origin of metaphysics and as its very possibility. In addition, the problem of how being and entities have been separated in the metaphysical tradition and why Heidegger calls this separation the "forgetfulness of difference" is analyzed. In contrast, conceiving the truth as arising from a split between the ontic and the ontological presents the possibility to see the ontological difference itself. An insight into the ontological difference and the conception of ontological truth open the possibility of re-wakening the Grundfrage, the question of ground, and to see the ground (reason) as an abyss (Ab-grund).